Blockade of Macrophage CD147 Protects Against Foam Cell Formation in Atherosclerosis - Lv, Jian-Jun; Wang, Hao; Cui, Hong-Yong; Liu, Ze-Kun; Zhang, Ren-Yu; Lu, Meng; Li, Can; Yong, Yu-Le; Liu, Man; Zhang, Hai; Zhang, Tian-Jiao; Zhang, Kun; et al. (Frontiers in Cell and Developmental Biology, 2021)
The persistence of macrophage-derived foam cells in the artery wall fuels atherosclerosis development. However, the mechanism of foam cell formation regulation remains elusive. We are committed to determining the role that CD147 might play in macrophage foam cell formation during atherosclerosis. In this study, we found that CD147 expression was primarily increased in mouse and human atherosclerotic lesions that were rich in macrophages and could be upregulated by ox-LDL. High-throughput compound screening indicated that ox-LDL-induced CD147 upregulation in macrophages was achieved through PI3K/Akt/mTOR signaling. Genetic deletion of macrophage CD147 protected against foam cell formation by impeding cholesterol uptake, probably through the scavenger receptor CD36. The opposite effect was observed in primary macrophages isolated from macrophage-specific CD147-overexpressing mice. Moreover, bioinformatics results indicated that CD147 suppression might exert an atheroprotective effect via various processes, such as cholesterol biosynthetic and metabolic processes, LDL and plasma lipoprotein clearance, and decreased platelet aggregation and collagen degradation. Our findings identify CD147 as a potential target for prevention and treatment of atherosclerosis in the future.